What past U.S. agency actions say about complexity in merger remedies, with an application to generic drug divestitures - Eric Emch; Thomas D. Jeitschko; Arthur Zhou (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2017)
We consider merger remedies of the U.S. Department of Justice's Antitrust Division and the U.S. Federal Trade Commission between 2008 and 2017. Traditionally one distinguishes between structural and behavioral remedies' and structural remedies are generally considered to be more effective and easier to implement. Our analysis suggests that over time this distinction has become somewhat blurred and a better gradation of remedies may be tied to the complexity of the proposed remedy. Divestitures in the market for generic drugs, in particular, are particularly complex, even though the remedies are of a structural, and so their efficacy is hard to ascertain.
Keywords: 330; Antitrust; Mergers; Structural Remedies; Behavioral Remedies; U.S. Enforcement